Assessment about bioindicator capacity of acrocarpous moss Campylopus schmidii exposed to abandoned pyritic tailings. (1st September 2022) - Zhang, Rong; Wang, Ziru; Huang, Huayan; Song, Jianjincang; Wu, Bohan; Wang, Maolin; Xu, Heng
Abstract: Terrestrial mosses are promising species to study concerning metal deposition, absorption, and soil fertility as moss biocrusts. However, acrocarpous moss, as a kind of terrestrial mosses, has not yet been well understood, both in environmental monitoring and ecological application, especially exposed to an abandoned pyrite mining. Herein, we investigated the concentrations of different heavy metals in soil underlying acrocarpous moss Campylopus schmidii at three distances from an abandoned pyrite mine tailings (0.5, 1, 2 km) by sampling analysis, as well as the accumulation properties of heavy metals in different parts of mosses and soil nutrients under intact mosses and moss-free layers. The results indicated that the soil we researched was heavily polluted by Cr, Cu, and Cd, which was 4.46, 4.18, and 1.77 times higher than the standard of risk screening values for soil environment quality in China. And there was a marked difference in the concentrations and distribution of heavy metals in mosses, with higher concentrations of Cr, Cu, Ni and Pb mainly in the ageing parts. In addition, mosses can effectively promote soil fertility. Compared with the bare soil without the moss layer, the total organic matter and total potassium concentrations of the soil covered by the intact moss layer were significantly increased, by 113.91% and 186.08% respectively. Correlation analysis indicated that similar pollution sources for Zn, Cd, Cu, and Pb, and the concentrations of these heavy metals in soil connected with the distance from the source of pollution. Overall, we expected that these findings could assess the greater potential of single native dominant moss species C.schmidii to act as biomonitors in specific pyrite mine tailings characterized by barren soil with strong acids (pH < 4.0) and polymetallic pollution. Meanwhile, our results revealed may serve as a possibility reference for similar areas and is recommended for developing a vegetative cover utilizing local acrocarpous mosses to achieve greening of degraded tailings in the future, as well as environmental management and protection. Graphical abstract: Image 1 Highlights: Campylopus schmidii grew in locations with heavily polluted by Cr, Cu, and Cd. Some heavy metals in soil connected with the distance from the source of pollution. The distribution of heavy metals in acrocarpous moss species varied markedly. Moss promotes soil fertility by enhanced soil nutrients compare to bare ground.